Antifungal Activity Test of Cinnamon Extract (Cinnamomun burmani) on Growth of Aspergillus flavus and Fusarium moniliforme - Vivi Novrianti; Israwati Harahap; Elsie Elsie (Bioscience, 2019)
The purpose of this research is to determine the activity of cinnamon extract (Cinnamomun burmani) as an antifungal against the growth of fungi Aspergillus flavus and Fusarium moniliforme. The procedure begins with making cinnamon extract obtained from cinnamon bark using rotary distillation method. Cinnamon extract will be tested using different concentrations of 0% (control); 0,5%; 1,0%; 2,0% and 4,0% with the well diffusion method. Based of the results, the cinnamon extract has antifungal activity against the fungi with the concentration and inhibition of 1,0% and inhibition zone diameter of 27 mm in A. flavus, while the concentration and inhibition of 2,0% with a inhibition zone of 56 mm in F. moniliforme.